Patient safety: antibiotics prescription review in pediatric patient - Chamim Faizin; Wiwik Kusumawati; Inayati Habib (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2019)
The patient safety incidents is closely related to treatment services. Medication errors in pediatric patients are generally three times higher than adult patients. 40.8% medication errors occur in prescribing drugs such as antibiotics. This study was to analyze the management of antibiotic prescribing in hospitalized pediatric patients at X Hospital for patient safety. This study used mixed methods namely quantitative by observational cross sectional and qualitative case study. It used a purposive sampling method with inclusion and exclusion criteria obtained from 494 medical record data from 2367 total patients in 2017. Analysis of the antibiotic rationality of the Gyssens method and deep interviews of pediatricians, pharmacists and patient safety management. The most antibiotic use is cefotaxime 51,83%. It used rational antibiotics (40.69%). The irrational antibiotics were in category V (22.8%), IVD category (25.10%), IIIA category (8.10%), IIC category (2.63%). Giving antibiotics rationally is not maximized so that it needs better regulation and systems. Patient safety incidents occur in patients' identity errors and LASA drugs (look-alike and sound-alike) do not cause serious incidents. Prescribing rational antibiotics in hospitalized pediatric patients has not been maximized and patient safety incidents are still found. Need support from management in optimizing rational antibiotic use programs as well as patient safety culture.